The Phenomenon of Curriculum Development Dynamics in Indonesia: Challenges, Adaptation, and Its Implications on Teacher Performance - Mursidi; Tolkhah Khuriza; Nurul Mubin (LP3M INSTITUT KH YAZID KARIMULLAH, 2026)
Curriculum development and change are inevitable in the education system to meet the demands of the times. However, for teachers who stand in front of their classrooms every morning, curriculum change is like a tectonic earthquake. There's a classic adage often heard cynically in the teachers' lounge: